Is Silence Golden? Patents versus Secrecy at the Firm Level - Katrin Hussinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
In the 1990s, patenting schemes changed in many respects: upcoming new technologies accelerated the shift from price competition towards competition based on technical inventions, a worldwide surge in patenting took place, and the ?patent thicket? arose as a consequence of strategic patenting. This study analyzes the importance of patenting versus secrecy as an effective alternative to protect intellectual property in the inventions? market phase. The sales figure with new products is introduced as a new measure for the importance of IP protection tools among product innovating firms. Focusing on the German manufacturing in 2000, it turns out that patents are important to protect intellectual property in the market, whereas secrecy seems to be rather important for early-stage inventions.
Keywords: O33; C35; C34; O34; 330; Innovation; Appropriation; Patents; Secrecy; Immaterialgüterrechte; Patent; Innovation; Geheimhaltung